KLF2 overrides the resident memory CD8 T cell differentiation program, in opposition to KLF3 - Taylor A. DePauw; Kexin Gai; Jian Shen; Nicholas J. Maurice; Ka Hyun Rhee; William J. Valente; Christine H. O’Connor; Weiguo Cui; Changwei Peng; Stephen C. Jameson (Proceedings of the National Academy of Sciences, 2026)
Numerous transcriptional regulators have been associated with the differentiation pathways that lead to recirculating vs. tissue-resident memory T cells. However, it is unclear whether independent, coordinated expression of these regulators is required to determine residency vs. recirculation or whether there is a hierarchy, with some factors playing a dominant role in controlling T cell trafficking. We report that ablation of the gene encoding Kruppel-like factor 2 (KLF2) during CD8 + T cell activation leads to rapid transcriptional reprogramming, such that effector T cells fail to recirculate and prematurely acquire canonical phenotypic and transcriptional characteristics of resident memory cells (T RM ). Klf2 -deficient memory CD8 + T cells retained the capacity to undergo recall responses, including in vivo pathogen control. These data suggest that KLF2 diverts CD8 + T cells from the T RM differentiation program. In contrast, ablation of another member of the KLF family, KLF3, enhanced differentiation of some recirculating T cell subsets and limited production of T RM in lymphoid tissues. However, both KLF2 and KLF3 were required for differentiation of long-lived effector cells, suggesting cooperation between these factors in some situations. These findings indicate that KLFs occupy a central nexus in coordinating activated CD8 + T cell differentiation and trafficking.